Implementasi Media Kofabar terhadap Kemampuan Membaca Permulaan Anak Kelompok B - Riswandi, Fitta Nurisma; Fitria, Fadilatul (Journal of Childhood Education, Development and Parenting, 2023)
This study aims to determine the implementation of cofabar media (alphabet boxes and pictures) on the beginning reading ability of group B children. The research method used was the One Group Pretest-Posttest Design experiment. The subjects of this study were the children of group B RA Ainul Huda, totaling 15 children and the sampling technique used purposive sampling. This study used an observation sheet consisting of 5 indicators in data collection. The data analysis technique used the non-parametric Wilcoxon Ranks Test. The results showed that Kofabar media was implemented in the beginning reading ability of group B children as evidenced by the results of a significance value of 0.001. While the results of the initial measurement and the final measurement of the beginning reading ability of group B children experienced a difference in the average score, the initial measurement was 27.92 and the average score at the end of the measurement was 50.73. The implementation in this study is that the cofabar media can be implemented by early childhood educators to stimulate the beginning reading skills of group B children Penelitian ini bertujuan untuk mengetahui implementasi media kofabar (Kotak alphabet dan gambar) terhadap kemampuan membaca permulaan anak kelompok B. Metode penelitian yang digunakan adalah eksperimen One Group Pretest-Posttest Design. Subyek penelitian ini yaitu anak kelompok B RA Ainul Huda yang berjumlah 15 anak dan teknik sampling menggunakan purposive sampling. Penelitian ini dalam pengumpulan datanya menggunakan lembar observasi yang terdiri dari 5 butir indikator, teknik analisis data menggunakan uji Wilcoxon Ranks Test non parametrik. Hasil penelitian menunjukkan media kofabar berimplementasi pada kemampuan membaca permulaan anak kelompok B yang dibuktikan dengan hasil nilai signifikasi 0.001. Sedangkan hasil pengukuran awal dan pengukuran akhir kemampuan membaca permulaan anak kelompok B mengalami perbedaan skor rata-rata, pengukuran awal sebesar 27.92 dan skor rata-rata pada pengukuran akhir sebesar 50.73. Implementasi dalam penelitian ini adalah media kofabar dapat diimpleemntasikan oleh pendidik anak usia dini untuk menstimulasi kemampuan membaca permulaan anak kelompok B